KAJIAN IT GOVERNANCE UNTUK PENINGKATAN PRODUKTIVITAS OPERASIONAL PELAYANAN PUBLIK - Ismi Kaniawulan , MT (Universitas Raharja, 2012)
Development of Information Technology as a strategic tool, it is important to use to maximize the potential of the company in increasing resources and targeting strategies. The public service as a business process menlibatkan citizens have a high complexity so that the utilization of information technology needs to be a requirement that is not inevitable. Application of information technology systems and governance in the public service into an absolute concept is implemented to increase productivity, effectiveness and efficiency. Productivity, customer service effectiveness refers to the achievement of customer satisfaction. Benchmark customer satisfaction in the context of public service seems quick response citizens in the government's performance when the service performed. The main focus of government is to be achieved prosperity,profitability and good governance. A series of IT Governance concepts are applied in this study adopts the IT service management. The constraints in the implementation of IT Governance in the public service is the influence of social, political and economic collaboration between organizations and concepts. This study is a study conducted to determine selanjutkan will be developed in IT Governance strategies of public service.